2002
DOI: 10.1111/j.1939-1676.2002.tb02386.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Clinical Evaluation of Serum Cardiac Troponin T in Dogs Admitted to a Veterinary Teaching Hospital

Abstract: The purpose of this study was to measure serum cardiac troponin T (cTnT) with a commercially available human enzyme-linked immunoassay (ELISA) test in various groups of dogs, including those undergoing doxorubicin chemotherapy. Serum samples were obtained from 6 groups of dogs: (1) normal adult dogs (n = 15); (2) dogs with asymptomatic dilated cardiomyopathy (n = 5); (3) dogs with congestive heart failure (n = 10); (4) dogs with untreated neoplasia (n = 20); (5) dogs with skeletal muscle trauma (n = 10); and (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 21 publications
5
27
0
1
Order By: Relevance
“…The absence of detectable cTnT (>0.05 ng/ml) in healthy dogs confirms the utility of this assay in assessing acute myocardial damage, similar to that reported both for both human and veterinary subjects (De Francesco, 2002). The results of the present work indicate the usefulness of the cTnT test for the identification of cardiopathic subjects for whom disease is associated with myocardial damage.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The absence of detectable cTnT (>0.05 ng/ml) in healthy dogs confirms the utility of this assay in assessing acute myocardial damage, similar to that reported both for both human and veterinary subjects (De Francesco, 2002). The results of the present work indicate the usefulness of the cTnT test for the identification of cardiopathic subjects for whom disease is associated with myocardial damage.…”
Section: Discussionsupporting
confidence: 89%
“…The degree of increase in the level of cTnT is relatively proportional to the degree of myocardial damage, with prognostic implications as well. At the same time, the extreme sensitivity of this technique also allows for its use in other nonischemic pathologies including chronic cardiac insufficiency, pulmonary emboli, acute myocarditis, systemic hypertension, arrhythmias, and toxicity from doxorubicin (De Francesco, 2002). In veterinary medicine, O'Brien et al (1997) have demonstrated the utility of measuring the levels of cTnT in the diagnosis of experimentally induced myocardial damage.…”
Section: Introductionmentioning
confidence: 99%
“…Analyses of cTn-T and cTn-I were performed with 2 different analyzer systems, e, f 1 of which e has been extensively used in several previous studies of dogs. [14][15][16][17][18] Serum cTn concentrations from the envenomed dogs were compared with reference ranges that were established for 10 clinically normal (staff-owned) control dogs.…”
Section: Clinicopathologic Datamentioning
confidence: 99%
“…In healthy dogs, blood levels of cardiac troponin T (cTn-T) or cTn-I are very low or below the level of detectability of most assay systems in both humans (11) and animals (5,9,14,28,32). The detection of high concentrations of circulating cTn-I is viewed as a specific indicator of myocardial injury and cellular necrosis (7,23).…”
Section: Discussionmentioning
confidence: 99%